Application of the asymptotic theory of extreme values to risk simulation of breaking-out of large forest fires - Kosygin, Vladimir Yu.; Katin, Viktor D.; Akhtyamov, Midkhat H.; Ilyavin, Mihail V. (Nexo Revista Científica, 2021)
Issues of applying the asymptotic theory of extreme values to the risks analysis of breaking-out of the largest-area yearly forest fires, were considered. As original material, the paper authors used data on areas of the forest fires occurring in the south of Russia’s Khabarovsk Territory from 1968 to 2017. For each year, the largest-area forest fire was selected from the considered period of time. In all, 50 fires were selected for this period of time (according to quantity of the years in the period). This sample analysis showed that the general population of these fires areas (where the sample was selected) has probability distribution of extreme values of the first type. An analytical expression for the probability distribution function of this general population was received. On the basis of this distribution analysis, a forecast was made concerning risks of the breaking-out and the average recurrence periods of such fires for various values of the burning area. The conducted analysis showed that in 87.5% of cases, in the south of Khabarovsk territory, the largest-area yearly forest fires, with an area of from 50 to 400 km2, will break out with the 1.2 years recurrence interval. In other words, almost every year, with the exception of these rare events when fires with other areas will occur. It was supposed that the probability distribution of extreme values of the first type can be applied not only to the forest area of Russia’s Khabarovsk territory, but also to other zones in the world with large forest areas.